Adaptive Correction from Virtually Complex Dynamic Libraries: The Role of Noncovalent Interactions in Structural Selection and Folding. Issue 47 (8th October 2015) - Lafuente, Maria; Atcher, Joan; Solà, Jordi; Alfonso, Ignacio
Abstract: The hierarchical self‐assembling of complex molecular systems is dictated by the chemical and structural information stored in their components. This information can be expressed through an adaptive process that determines the structurally fittest assembly under given environmental conditions. We have set up complex disulfide‐based dynamic covalent libraries of chemically and topologically diverse pseudopeptidic compounds. We show how the reaction evolves from very complex mixtures at short reaction times to the almost exclusive formation of a major compound, through the establishment of intramolecular noncovalent interactions. Our experiments demonstrate that the systems evolve through error‐check and error‐correction processes. The nature of these interactions, the importance of the folding and the effects of the environment are also discussed. Abstract : Fix it! Error‐check and error‐correction processes allow the exploration and establishment of the essential interactions that drive the molecular evolution of complex libraries of compounds to the formation of almost exclusively a single compound (see figure).